Effects of Fe2O3 addition and annealing on the mechanical and dissolution properties of MgO- and CaO-containing phosphate glass fibres for bio-applications - Tan, Chao; Ahmed, Ifty; Parsons, Andrew J.; Zhu, Chenkai; Betanzos, Fernando B. (De Gruyter Open, 2018)
This paper investigated the preparation of phosphate glass fibres (PGFs) in the following systems: i) 45P2O5-5B2O3-5Na2O-(29-x)CaO-16MgO-(x)Fe2O3and ii) 45P2O5-5B2O3-5Na2O-24CaO-(21-x)MgO-(x)Fe2O3(where x = 5, 8 and 11 mol%) for biomedical applications. Continuous fibres of 23 ± 1 μm diameter were prepared via a melt-draw spinning process. Compositions with higher Fe2O3content and higher MgO/CaO ratio required higher melting temperature and longer heating time to achieve glass melts for fibre pulling. The effects of Fe2O3 addition and annealing treatment on mechanical properties and degradation behaviours were also investigated. Adding Fe2O3 was found to increase the tensile strength from 523 ± 63 (Ca-Fe5) to 680 ± 75 MPa (Ca-Fe11), improve the tensile modulus from 72 ± 4 (Ca-Fe5) to 78 ± 3 GPa (Ca-Fe11) and decrease the degradation rate from 4.0 (Mg-Fe5) to 1.9 × 10-6kg m-2s-1(Mg-Fe11). The annealing process reduced the fibre tensile strength by 46% (Ca-Fe5), increased the modulus by 19.6% (Ca-Fe8) and decreased the degradation rate by 89.5% (Mg-Fe11) in comparison to the corresponding as-drawn fibres. Additionally, the annealing process also impeded the formation of precipitate shells and revealed coexistence of the precipitation and the pitting corrosion as fibre degradation behaviours.